2022
DOI: 10.2147/idr.s386345
|View full text |Cite
|
Sign up to set email alerts
|

NDM-1 and OXA-48-Like Carbapenemases (OXA-48, OXA-181 and OXA-252) Co-Producing Shewanella xiamenensis from Hospital Wastewater, China

Abstract: Background Shewanella genus, as an important carrier of resistance genes, has the potential to transmit resistance to many antimicrobials in many circumstances, especially in aquatic environment. The aim of the study was to describe the risk of Shewanella xiamenensis in hospital environment through analysis of genomic comparison and resistance status. Methods Seven S. xiamenensis strains were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…At present, significant changes in the antibiotic resistance of S. xiamenensis have been unraveled. Recently, S. xiamenensis carrying bla NDM−1 or tet (X4) have been reported in China and Vietnam, respectively [ 8 , 9 ]. The resistance against last-line antibiotics like carbapenems and tigecycline indicated that the gene pool of S. xiamenensis has significantly expanded, making it become a reservoir of antibiotic resistance genes in aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
“…At present, significant changes in the antibiotic resistance of S. xiamenensis have been unraveled. Recently, S. xiamenensis carrying bla NDM−1 or tet (X4) have been reported in China and Vietnam, respectively [ 8 , 9 ]. The resistance against last-line antibiotics like carbapenems and tigecycline indicated that the gene pool of S. xiamenensis has significantly expanded, making it become a reservoir of antibiotic resistance genes in aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
“…are relatively low compared to Enterobacteriaceae, bla NDM , bla SHV , bla CTX-M , qnr A, cat A, dfr A, and tet cluster genes have been reported in Shewanella spp. [ 47 , 48 , 49 , 50 , 51 ]. It is clear that the emergence of multiple drug-resistant Shewanella spp., especially those containing bla OXA-48 -like genes, poses a significant threat to clinical treatment [ 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The A. veronii strain, HD6454, was isolated from the raw sewage in sewage conduit under washbasin in digestive department of the Second Affiliated Hospital of Soochow University (Suzhou, China) in July 2019. The detailed isolation methodology was described previously ( Wen et al, 2022 ). Bacterial species identification was carried out using Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS).…”
Section: Methodsmentioning
confidence: 99%